2015
DOI: 10.1021/acs.molpharmaceut.5b00598
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cell-Penetrating Peptide/Nucleic Acid Nanoparticles

Abstract: Nucleic acids are highly promising candidates for the treatment of various genetic diseases. However, due to the large size and negative charge, nucleic acids are not efficiently taken up by cells, and thus, their clinical potential remains limited so far. Therefore, various delivery vehicles have been designed to assist the cellular uptake of nucleic acids. Among these, cell-penetrating peptides (CPPs) have gained increasing popularity as efficient and nontoxic delivery vectors. CPPs can be coupled to nucleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Small polar molecules, such as ions, amino acids, and monosaccharides, are able to enter cells through specific carriers or channels in the plasma membrane. The intrinsic nature of cellular membranes precludes influx of macromolecules, such as DNAs, RNAs, and proteins [ 1 ]. Several strategies have been developed to deliver exogenous macromolecules across cellular membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small polar molecules, such as ions, amino acids, and monosaccharides, are able to enter cells through specific carriers or channels in the plasma membrane. The intrinsic nature of cellular membranes precludes influx of macromolecules, such as DNAs, RNAs, and proteins [ 1 ]. Several strategies have been developed to deliver exogenous macromolecules across cellular membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-penetrating peptides (CPPs) that can deliver therapeutic and diagnostic molecules into cells in a nontoxic manner have recently received considerable attention as a promising nonviral tool for the delivery of drugs and diagnostic agents [ 1 , 2 ]. The first CPP discovered, transactivator of transcription (Tat)-protein transduction domain (PTD), consists of eleven amino acids (YGRKKRRQRRR) of the HIV-1 Tat.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the difference in stability to degradation may be caused by the particle properties. Transmission electron microscopy analysis showed that PF6/siRNA particles were tightly packed and almost perfectly spherical as are particles with NFs, but PF14 formed oval shaped particles with a larger surface area exposed to enzymes 40 . The stability of PFs to heparin displacement and serum has been compared to CPPs R9 and Tat, 41 and the results indicated that an optimal stability to heparin displacement and a high stability to serum could be crucial for higher delivery efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Cell‐penetrating peptides (CPPs) are short peptides composed of fewer than 30 amino acids that transport a variety of different bioactive molecules including peptides, proteins, nanoparticles, DNA, small interfering RNA, liposomes, and small molecule therapeutics into living cells. Most CPP sequences contain basic amino acid residues that are positively charged in a physiological environment to allow them to adhere to negatively charged cell membranes, and the hydrophobic residues of these CPPs interact with the lipid bilayer of the cell membrane, resulting in the cargo molecules carried by the CPP being transported into the cell by endocytosis .…”
Section: Introductionmentioning
confidence: 99%